Stylistic features zvukopysu poetic speech in Ukrainian poets of the early twentieth century (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2011)
The article defines reviewed and analyzed stylistic features zvukopysu in the individual style of famous poets of the early twentieth century. Based on the illustrations show the role of onomatopoeia, as one of the methods zvukopysu.
Keywords: zvukopys; stylistic features; fonostylistyka; individual style; onomatopoeia